2021
DOI: 10.1021/acs.orglett.1c01622
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Selective Modification of Secondary Amides: Application in Late-Stage Diversification of Peptides

Abstract: Here we solve a long-standing challenge of the siteselective modification of secondary amides and present a simple twostep, metal-free approach to selectively modify a particular secondary amide in molecules containing multiple primary and secondary amides. Density functional theory (DFT) provides insight into the activation of C−N bonds. This study encompasses distinct chemical advances for late-stage modification of peptides thus harnessing the amides for the incorporation of various functional groups into n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…Under metal-free conditions, a broad scope of CO 2 -promoted transamidation was achieved, particularly with Weinreb amides as a versatile amide donor. We believe that nontoxicity, inexpensiveness, and high availability of CO 2 is attractive as an inert atmosphere for organic reactions, particularly with peptide-based molecules and polymers in selective modification and degradation reactions …”
Section: Discussionmentioning
confidence: 99%
“…Under metal-free conditions, a broad scope of CO 2 -promoted transamidation was achieved, particularly with Weinreb amides as a versatile amide donor. We believe that nontoxicity, inexpensiveness, and high availability of CO 2 is attractive as an inert atmosphere for organic reactions, particularly with peptide-based molecules and polymers in selective modification and degradation reactions …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study from our group, DFT calculations on these synthons 1a−1d confirmed that the addition of carbonyl and thiocarbonyl groups led to the resonance destabilization that weakened the C−N amide bond, thus greatly enhancing its reactivity and availability for further modification (Figure 2a). 41 Using B3LYP/6-311+ +G(d,p) in our previous study, we also determined their amide bond distortion using Winkler−Dunitz parameters: twist angles (τ), pyramidization at nitrogen (X N ), and N− C(O) and C�O bond lengths. 41,42 We found that the addition of carbonyl or thiocarbonyl group between the side chain of serine and backbone C−N amide bond generated oxazolidinone 1a (τ = 21.30, X N = 9.1) and oxazolidithione 1b (τ = 24.0, X N = 16.1) and resulted in the twisting of the amide bond relative to the unmodified analog E (τ = 3.6, X N = 0.5) (Figure 2a).…”
Section: Selective Activation Of Amidesmentioning
confidence: 99%
“…41,42 We found that the addition of carbonyl or thiocarbonyl group between the side chain of serine and backbone C−N amide bond generated oxazolidinone 1a (τ = 21.30, X N = 9.1) and oxazolidithione 1b (τ = 24.0, X N = 16.1) and resulted in the twisting of the amide bond relative to the unmodified analog E (τ = 3.6, X N = 0.5) (Figure 2a). 41 Similarly, the addition of carbonyl and thiocarbonyl to cysteine generated twisted thiazolidinone 1c…”
Section: Selective Activation Of Amidesmentioning
confidence: 99%
“…However, amidic resonance decreases the reactivity towards nucleophilic addition, rendering transamidation a challenging task. [5,[9][10][11] Furthermore, transamidation with weakly nucleophilic aromatic amines turned transamidation an uphill task. Therefore, to achieve the task, harsh conditions such as high reaction temperature, long reaction time, or stoichiometric number of activating agents were employed to realize transamidation.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, transamidation has been developed as a viable alternate for amide bond formation. However, amidic resonance decreases the reactivity towards nucleophilic addition, rendering transamidation a challenging task [5,9–11] . Furthermore, transamidation with weakly nucleophilic aromatic amines turned transamidation an uphill task.…”
Section: Introductionmentioning
confidence: 99%